2016
DOI: 10.14405/kjvr.2016.56.4.205
|View full text |Cite
|
Sign up to set email alerts
|

Serum serotonin concentration in lean and obese dogs with myxomatous mitral valve disease

Abstract: Abstract:The aim of the present study is to investigate the potential influence of obesity as a factor in 5-hydroxytryptamine (5-HT) concentration in myxomatous mitral valve disease (MMVD) dogs. Fifty-five client-owned dogs were enrolled in a randomized trial. Dogs were classified by echocardiography into healthy (control), mild, and moderate to severe MMVD groups. Each group was subclassified by using a 9-point body condition score (BCS); lean (BCS 5-6/9) and obese groups (BCS 7.5-9/9). Dogs with moderate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A negative correlation between thrombocytic SRT and increasing plasma and serum SRT levels has also been described in humans. Due to the evidenced effects of SRT, most authors consider SRT to be one of the factors causing the development of MMVD [131][132][133][134], however, recent studies have not shown a clear role of SRT pathway gene expression in the development of PH in dogs, but have indicated increased protein synthesis of tryptophan hydroxylase 1 (TPH-1) and 5-hydroxytryptamine (serotonin) receptor 2a (5-HTR2A) in the MMVD and MMVD + PH states relative to the control group [97].…”
Section: Serotoninmentioning
confidence: 99%
“…A negative correlation between thrombocytic SRT and increasing plasma and serum SRT levels has also been described in humans. Due to the evidenced effects of SRT, most authors consider SRT to be one of the factors causing the development of MMVD [131][132][133][134], however, recent studies have not shown a clear role of SRT pathway gene expression in the development of PH in dogs, but have indicated increased protein synthesis of tryptophan hydroxylase 1 (TPH-1) and 5-hydroxytryptamine (serotonin) receptor 2a (5-HTR2A) in the MMVD and MMVD + PH states relative to the control group [97].…”
Section: Serotoninmentioning
confidence: 99%